Effects of Aerobic Exercise on Rats with Hyperandrogenic Polycystic Ovarian Syndrome - Na Li; Chenghao Yang; Huiyu Xie; Yinghong Liu; Yuanpeng Liao (International Journal of Endocrinology)
Hyperandrogenism is a key pathologic characteristic of polycystic ovarian syndrome (PCOS), and exercise can alleviate the accompanying inflammation and decrease the high androgen levels, but the mechanism is still unclear, so the purpose of this study is to explore the pathophysiologic characteristics of hyperandrogenic PCOS and the mechanism underlying its amelioration with aerobic exercise. Thirty-two female rats were randomly allocated to a normal control group (NC, n = 8), exercise control group (EC, n = 8), PCOS group (PC, n = 8), and PCOS plus exercise group (PE, n = 8). The PC and PE groups were injected with a dehydroepiandrosterone (DHEA) solution to induce the hyperandrogenic PCOS rat model. The EC and PE groups underwent a Masashi swimming protocol (120 min per session, 6 days/week, for 15 days). Results indicated that the concentrations of leptin (LP) in the EC group were significantly lower than those in the NC group (p<0.05). Compared with the NC group, the levels of testosterone (T), estradiol (E2), follicle-stimulating hormone (FSH), LP, anti-Müllerian hormone (AMH), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and free fatty acids (FFA) were all significantly augmented in the PC group (all p<0.05). In addition, compared with the NC group, the levels of adiponectin (ADP) were significantly decreased (p<0.05), and the expression of aromatase cytochrome P450 (P450arom) in ovarian tissue was significantly elevated in the PC group (p<0.05). The levels of T, FSH, LP, and FFA were also significantly increased in the PE group (p<0.05). Compared with the PC group, the levels of T and LP in the PE group were significantly diminished (p<0.05), and the levels of ADP were significantly increased in the PE group (p<0.05). T was positively correlated with E2, FSH, AMH, LP, TNF-α, IL-6, and FFA levels, while ADP was negatively correlated with LP and E2. These results showed that hyperandrogenism, chronic low-grade inflammation, and leptin resistance may interact to influence the occurrence and development of PCOS. Aerobic exercise can alleviate the internal inflammation by relieving leptin resistance and may mitigate the sex hormone disorder and hyperandrogenism in rats with PCOS by affecting the hypothalamic-pituitary-ovarian axis.